Degrees of success : the transitions from vocational to higher education - Hayward, Geoff; Katartzi, Eugenia; Ertl, Hubert; Hoelscher, Michael (Great debates in higher education., 2021)
Policies to promote high participation in Higher Educations (HE) systems aim to deliver social justice and economic development through widening participation of under-represented groups. Degrees of Success provides a critical test of this through examination of participation and success of learners progressing to HE with a vocational background. Employing an original conceptual framework that combines the ideas of Basil Bernstein and Pierre Bourdieu the authors analyse the various transitional frictions experienced by learners with VET backgrounds on their journeys into and through the HE system. The findings indicate that including students with vocational qualifications does lead to widening participation but that their modes of participation may not provide fair access and outcomes. In part this is due to the epistemic incompatibilities between higher and vocational education which remain unresolved despite constant VET qualification reform. This book, therefore, extends the debate about widening participation beyond metaphors of barriers to access to consider the epistemic and pedagogical challenges of increasing student heterogeneity in high participation HE systems. The analysis and policy suggestions therefore have relevance for all seeking to support students' HE learning journeys, and policy makers concerned with how best to utilise HE systems as means of furthering social mobility and justice.